Osteoporosis risk factors and association with somatotypes in males - Saitoglu, Mahmut; Ardicoglu, Ozge; Ozgocmen, Salih; Kamanli, Ayhan; Kaya, Arzu (Elsevier Science Inc, 2007)
Background. Osteoporosis is a systemic and metabolic skeletal disease characterized by reduced bone mass, changes in microarchitecture, and consequential increased fracture risk. Previous reports described a relationship between bone content with fat mass and lean body mass. In this study, we assessed osteoporosis risk factors and the association with somatotypes in males aged 45-65 years. Methods. Standard axial spine and proximal femur bone mineral density (BMD) were measured using dual x-ray (DXA) absorptiometry in 70 healthy men. Heath-Carter procedure was followed to assess individual's somatotype. Results. All body types were grouped as endomorphy, mesomorphy, and ectomorphy. Moderate to weak correlations were found between lumbar BMD with endomorphy and mesomorphy. Negative correlation was found between lumbar BMD and ectomorphy. Total femur BMD correlated positively with endomorphy and mesomorphy and negatively correlated with ectomorphy. Body mass index correlated weakly with lumbar, femur neck, and total femur BMD. Multiple regression analysis revealed that endomorphy was significantly related to BMD measurements at lumbar spine (standardized coefficient, SC = 0.5 1 p = 0.001), femur neck (SC = 0.52, p = 0.001), and total femur BMD (SC = 0.4 1, p = 0.01). Lumbar BMD and age, hand grip strength, smoking, tea and coffee consumption, calorie expenditure, calcium intake, PTH, albumin, total protein, sex hormone-binding globulin, and testosterone were not significantly correlated. Conclusions. Endomorphy seems related to high BMD values at the lumbar spine and the proximal femur in middle-aged men. Somatotype together with daily calorie expenditure may be taken into account when assessing risk factors for male osteoporosis. (c) 2007 IMSS. Published by Elsevier Inc.
Keywords: osteoporosis; male; risk factors; somatotype; bone mineral density